2012
DOI: 10.1111/j.1095-8649.2012.03242.x
|View full text |Cite
|
Sign up to set email alerts
|

An overview on the role of Hexanchiformes in marine ecosystems: biology, ecology and conservation status of a primitive order of modern sharks

Abstract: The large size, high trophic level and wide distribution of Hexanchiformes (cow and frilled sharks) should position this order as important apex predators in coastal and deep‐water ecosystems. This review synthesizes available information on Hexanchiformes, including information not yet published, with the purpose of evaluating their conservation status and assessing their ecological roles in the dynamics of marine ecosystems. Comprising six species, this group has a wide global distribution, with members occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
70
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 58 publications
1
70
0
Order By: Relevance
“…vitulus) did not reveal any distinctive differences between those from the western North Atlantic and the western North Pacific (Ebert, 1990). Taniuchi & Tachikawa (1991) followed in synonymising the two species with H. nakamurai being the senior synonym and most subsequent authors considering the two species to be synonymous (Last & Stevens, 1994, 2009Compagno et al, 2005;Barnett et al, 2012;Ebert & Stehmann, 2013;. Herman et al (1994) later resurrected H. vitulus as a valid species separable from H. nakamurai based on the following odontological differences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…vitulus) did not reveal any distinctive differences between those from the western North Atlantic and the western North Pacific (Ebert, 1990). Taniuchi & Tachikawa (1991) followed in synonymising the two species with H. nakamurai being the senior synonym and most subsequent authors considering the two species to be synonymous (Last & Stevens, 1994, 2009Compagno et al, 2005;Barnett et al, 2012;Ebert & Stehmann, 2013;. Herman et al (1994) later resurrected H. vitulus as a valid species separable from H. nakamurai based on the following odontological differences.…”
Section: Methodsmentioning
confidence: 99%
“…Size at birth is about 40 to 43 cm TL. Barnett et al (2012) provides an overview on the biology of this little known species. Compagno (1984) commented that comparison of the original descriptions of H. griseus nakamurai and H. vitulus strongly suggested that these two species were synonymous, but he did not have any specimens with which to A B C compare these two nominal species directly.…”
Section: Methodsmentioning
confidence: 99%
“…Such conditions coincide with the known habitat of H. griseus in its area of distribution, i.e., hypoxic environments with low temperature and high hydrostatic pressure (Compagno, 1984;Barnett et al, 2012). Although this species mainly inhabits the continental slope, juveniles have been reported to make incursions into neritic environments (over the continental shelf) during the night, when they undergo vertical migration possibly related to feeding (Compagno, 1984;Andrews et al, 2007Andrews et al, , 2009Andrews et al, , 2010Comfort, 2012).…”
mentioning
confidence: 99%
“…In Mexico, information relative to H. griseus is insufficient for realize a proper assessment of the status of its population; furthermore, the limited information on its reproductive biology suggests that this taxon may be vulnerable to fishing (Barnett et al, 2012). The punctual catches recording of H. griseus taking advantage of them to produce scientific knowledge about basic aspects of its biology, will allow better understanding of the ecological niche occupied by this species in the national territory.…”
mentioning
confidence: 99%
See 1 more Smart Citation